2012
DOI: 10.1111/j.1469-0691.2012.03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus infection: patterns of fetal brain damage

Abstract: Cytomegalovirus (CMV) is the most prevalent infectious agent causing neurological dysfunction in the developing brain. This study analysed the different patterns of tissue damage, particularly in the brain, of fetuses with documented CMV infection. We studied 45 fetuses at 20-21 weeks of gestation with congenital CMV infection documented by invasive positive prenatal diagnosis. At the time of amniocentesis, abnormal ultrasound findings had been recorded for 13 of the 45 fetuses (29%). Histological and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
106
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 27 publications
18
106
1
1
Order By: Relevance
“…Viral load in placentas was determined as described previously. 15 CD3+, CD4+, CD8+, CD56+, and CD19+ lymphocyte counts were determined at each study visit. Surface phenotype (in the case of CD4+ and CD8+ lymphocytes) as well as interferon-γ-producing CMV-specific T cells were determined retrospectively by means of flow cytometry, as described previously.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Viral load in placentas was determined as described previously. 15 CD3+, CD4+, CD8+, CD56+, and CD19+ lymphocyte counts were determined at each study visit. Surface phenotype (in the case of CD4+ and CD8+ lymphocytes) as well as interferon-γ-producing CMV-specific T cells were determined retrospectively by means of flow cytometry, as described previously.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Histological studies of tissue from fetuses and infants with fatal congenital HCMV have demonstrated mononuclear cell (MNC) infiltrates in the CNS, suggesting that host inflammatory responses contribute to the pathogenesis of infection (11,(23)(24)(25). Moreover, these studies also described a limited number of virus-infected cells within the CNS, indicating that virus-induced cellular cytopathology cannot account for the global and, importantly, the symmetric involvement of the brain in congenitally infected infants (11,(23)(24)(25).…”
mentioning
confidence: 99%
“…In the present study, hearing problems was not detected among neurological manifestations in symptomatic HCMV infected neonates. A large number of hearing problems that result from HCMV infection was detected at school age (39) , which may be attributed to misdiagnosis of hearing problems among neonates in this study. Petechial rash was described in 20% of the symptomatic HCMV infected neonates, which was found to be lower than those recorded by others: 33.3% and 32% (40) .…”
Section: Discussionmentioning
confidence: 95%